Theileria: Intracellular protozoan parasites of wild and domestic ruminants transmitted by ixodid ticks - Bishop, Richard P.; Musoke, A.J.; Morzaria, S.P.; Gardner, M.; Nene, Vishvanath M. (Cambridge University Press, 2004)
Theileria are economically important, intra-cellular protozoa, transmitted by ixodid ticks, which infect wild and domestic ruminants. In the mammalian host, parasites infect leukocytes and erythrocytes. In the arthropod vector they develop in gut epithelial cells and salivary glands. All four intra-cellular stages of Theileria survive free in the cytoplasm. The schizont stages of certain Theileria species induce a unique, cancer-like, phenotype in infected host leukocytes. Theileria undergoes an obligate sexual cycle, involving fusion of gametes in the tick gut, to produce a transiently diploid zygote. The existence of sexual recombination in T. parva has been confirmed in the laboratory, and is presumed to contribute to the extensive polymorphism observed in field isolates. Key parameters in T. parva population dynamics are the relative importance of asymptomatic carrier cattle and animals undergoing severe disease, in transmission of the parasite to ticks, and the extent of transmission by nymphs as compared to adult ticks. Tick populations differ in vector competence for specific T. parva stocks. Recombinant forms of T. parva and T. annulata sporozoite surface antigens induce protection against parasite challenge in cattle. In future, vaccines might be improved by inclusion of tick peptides in multivalent vaccines.